A novel variant in COX16 causes cytochrome c oxidase deficiency, severe fatal neonatal lactic acidosis, encephalopathy, cardiomyopathy, and liver dysfunction. Issue 2 (30th November 2020) - Wintjes, Liesbeth T. M.; Kava, Maina; van den Brandt, Frans A.; van den Brand, Mariël A. M.; Lapina, Oksana; Bliksrud, Yngve T.; Kulseth, Mari A.; Amundsen, Silja S.; Selberg, Terje R.; Ybema‐Antoine, Marion; Tutakhel, Omar A. Z.; Greed, Lawrence; et al.
Abstract: COX16 is involved in the biogenesis of cytochrome‐c‐oxidase (complex IV), the terminal complex of the mitochondrial respiratory chain. We present the first report of two unrelated patients with the homozygous nonsense variant c.244C>T(p. Arg82*) in COX16 with hypertrophic cardiomyopathy, encephalopathy and severe fatal lactic acidosis, and isolated complex IV deficiency. The absence of COX16 protein expression leads to a complete loss of the holo‐complex IV, as detected by Western blot in patient fibroblasts. Lentiviral transduction of patient fibroblasts with wild‐type COX16 complementary DNA rescued complex IV biosynthesis. We hypothesize that COX16 could play a role in the copper delivery route of the COX2 module as part of the complex IV assembly. Our data provide clear evidence for the pathogenicity of the COX16 variant as a cause for the observed clinical features and the isolated complex IV deficiency in these two patients and that COX16 deficiency is a cause for mitochondrial disease. Abstract : We present the first report of two unrelated patients with the homozygous nonsense variant c.244C>T(p. Arg82*) in COX16 with hypertrophic cardiomyopathy, encephalopathy and severe fatal lactic acidosis, and isolated complex IV deficiency. Our data provide clear evidence for the pathogenicity of the COX16 variant as a cause for the observed clinical features and the isolated complex IV deficiency in these two patients and that COX16 deficiency is a cause for mitochondrial disease.